2017
DOI: 10.1007/978-3-319-68210-5_5
|View full text |Cite
|
Sign up to set email alerts
|

TCon: A Transparent Congestion Control Deployment Platform for Optimizing WAN Transfers

Abstract: Nowadays, many web services (e.g., cloud storage) are deployed inside datacenters and may trigger transfers to clients through WAN. TCP congestion control is a vital component for improving the performance (e.g., latency) of these services. Considering complex networking environment, the default congestion control algorithms on servers may not always be the most efficient, and new advanced algorithms will be proposed. However, adjusting congestion control algorithm usually requires modification of TCP stacks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Mystique should allow network administrators or operators to enforce advanced congestion controls without touching TCP stacks of servers. Deployment and operations of Mystique should be transparent to both web servers and clients [12,15,20]. Besides, Mystique should be able to apply different congestion controls on a perflow basis and switch congestion control according to current network status, and consume as less resource as possible.…”
Section: Design Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mystique should allow network administrators or operators to enforce advanced congestion controls without touching TCP stacks of servers. Deployment and operations of Mystique should be transparent to both web servers and clients [12,15,20]. Besides, Mystique should be able to apply different congestion controls on a perflow basis and switch congestion control according to current network status, and consume as less resource as possible.…”
Section: Design Principlesmentioning
confidence: 99%
“…Recent years have seen many Web applications moved into cloud datacenters to take advantage of the economy of scale. It is well known that Web latency inversely correlates with revenue and profit [20]. Reducing latency is of profound importance for providers [7].…”
Section: Introductionmentioning
confidence: 99%
“…With extensive experimental evaluations, it is demonstrated that BBR can achieve high throughput and low latency [3]. Some studies show that BBR work quite well for a single flow at a bottleneck [1] [3] [4].…”
Section: Introductionmentioning
confidence: 99%